Emerging fungal contaminants isolated and identified from raw fennel seeds - Abraham, Chinju Merin; Thomas, Tincy Mary (International Journal of Scientific Research in Biological Sciences, 2018)
The present investigation entitled “Emerging fungal contaminants isolated and identified from raw fennel seeds” recorded the diversity of surface contaminant fungi from 144 fennel seeds of different A/C and non-A/C hotels of town area of Pathanamthitta district of Kerala, which were cultured on PDA medium. All fungal species were identified on the basis of their morphological and microscopic characteristics and it includes Aspergillus niger, Aspergillus fumigatus, Chrysonilia sitophila, Mucor sp., Rhizopus sp., Cercospora sp. and Cylindrocarpon sp. The study revealed its colonization frequency, counted the fungal colony numbers, determined the percentage of different fungal isolates and finally compared the A/C and non-A/C seed contaminants. And from the study, it was clear that samples from non-A/C hotels shows maximum fungal growth than A/C hotels. These emerging fungal contaminants can cause serious pathogenic conditions such as aspergillosis, zygomycosis, occupational asthma etc.